14th International Energy Conversion Engineering Conference 2016
DOI: 10.2514/6.2016-5016
|View full text |Cite
|
Sign up to set email alerts
|

Improving Power Density of Free-Piston Stirling Engines

Abstract: Analyses and experiments demonstrate the potential benefits of optimizing piston and displacer motion in a free-piston Stirling Engine. Isothermal analysis shows the theoretical limits of power density improvement due to ideal motion in ideal Stirling engines. More realistic models based on nodal analysis show that ideal piston and displacer waveforms are not optimal, often producing less power than engines that use sinusoidal piston and displacer motion. Constrained optimization using nodal analysis predicts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The volume of working fluid rises quadratically as the radius of the Stirling engine rises, whereas the heat transfer space to the working fluid only grows linearly. The Stirling cycle is therefore reduced to the Otto cycle, often known as the adiabatic Stirling cycle [24].…”
Section: Ideal Stirling Cyclementioning
confidence: 99%
“…The volume of working fluid rises quadratically as the radius of the Stirling engine rises, whereas the heat transfer space to the working fluid only grows linearly. The Stirling cycle is therefore reduced to the Otto cycle, often known as the adiabatic Stirling cycle [24].…”
Section: Ideal Stirling Cyclementioning
confidence: 99%
“…In this theoretical study we focus on how the piston motion influences the engine performance by applying methods similar to previous optimizations of Stirling engines' piston motions [7][8][9][10][11][12][13]. Experimental studies [14,15] have shown that power output improvements of Stirling engines are feasible through altering the piston motion.…”
Section: Introductionmentioning
confidence: 99%